Efeito de lente térmica produzido por laser para a avaliação das propriedades ópticas e térmicas e da presença de adulterantes na bebida do café - Fontes, Adriana da Silva (2000)
The mechanism responsible for the physical and chemical properties of coffee’s brews has not been completely understood mainly due to its complex composition. Furthermore, it is frequent the presence of adulterants in the Brazilian commercial coffee, which has motivated the introduction of a seal of quality in order to control the purity of the product The optical microscopy is the main current method used to detect these contaminants. This technique can only be applied in powder samples and it has a limit of detection above 2 wt %. Therefore, the development of new sensitive methods to study both the physical and chemical properties and the presence of adulterants in coffee brews is of outmost importance. Thermal lens spectrometry is a powerful technique to study thermo-optical properties of transparent liquids. This technique is non-destructive, is simple to be used and can provide the absolute values of the thermo-optical properties of transparent samples. The aim of this work was to apply, for the first time, thermal lens spectrometry to determine the thermo-optical properties of the coffee brews. Furthermore, combining TLS with pH and spectrophotometric measurements the presence of adulterants in the coffee brews was detected. The experiments were performed in both pure commercial coffee and coffee mixed with 4 wt % of toasted corn meal. The concentration of the investigated samples, pure and adulterated, varied in the range from 0.04 wt % to 20 wt %. TL measurements provided the values of the parameter dn/dT ( temperature coefficient of the refractive index of the samples). Furthermore, combining this technique with pH and optical absorption coefficient measurements the presence of adulterants in the coffee brew was investigated. The experiments were performed at room temperature, immediately after the preparation of the coffee brew. The dn/dT data plotted against coffee concentration showed that this parameter changed in such a way that it can be described by an inverse pulse curve with a minimum at about 0.6 wt %. These results indicate that in the range of low concentration a decrease in the value of the temperature coefficient of the electronic polarizability (ϕ) occurs as a consequence of the possible dissociation of the water aggregates during the coffee percolation process. For concentrations higher than 0.6 wt %, the increase of dn/dT values can be described by an exponential growth curve saturating around 6 wt %. Likewise, pH data as a function of the coffee concentration can be also described by an inverse pulse curve. This suggests that in the low range concentration the amount of free charges in the solution increases, probably due to the dissociation of the solution’s complexes. Therefore, the results of both dn/dT and pH are in agreement with respect to the changes in the amount of free charges in the sample when the concentration is modified. By performing an exponential fitting in the results of dn/dT we have observed that the value of the parameter, t1, which describes the variation of dn/dT as a function of coffee concentration differs when the results for pure and adulterated coffee are compared. This procedure was also followed in the pH measurements data and again we were able to differentiate pure coffee brew from the adulterated one. Therefore, both results for dn/dT and pH measurements have show that combination of these methods can be successfully applied to detect adulterants in coffee by investigation of the brew. This is the first time that the Thermal lens spectrometry is applied to investigate coffee beverage. The results have shown that this technique can be used to determine the thermo-optical properties of coffee, which is one of the most important product of our economy. Regarding the presence of adulterants, our results indicate that this technique may be an useful method to study other industrialized foods like oils.